“Likes” for history on Instagram: some questions about history, teaching and representation (Olhar de Professor, 2021)
The article discusses a set of 21 images published on the social network Instagram on August 19th - Historian's Day - to analyze some representations circulated about History in the posts. In the methodological procedure, the images were selected at random on August 19, 2020 using the profiles followed by the laboratory and research group (iTemnpo) through its account @itemnpo. Then the images were categorized into three types: a) “authorship of the posted content” b) “profile typology” and c) “referentiality”. Through the analyzed posts, it is possible to perceive a representation of History focused only on its academic dimension, being presented predominantly by images of male, European researchers and unrelated to the History teaching.
Keywords: History. Representation. Social networks. History teaching.